(untitled) (Physical Education, Health and Social Sciences, 2026)
Background: Precise evaluation of hyperopia is crucial for correct diagnosis and treatment, particularly in youngsters when accommodation may conceal underlying hyperopia. In this study, hyperopic children and adults’ cycloplegic and non-cycloplegic refraction was examined. Objective: To assess the extent of latent hyperopia and its clinical importance, as well as to compare cycloplegic and non-cycloplegic refraction in hyperopic children and adults. Methodology: 114 hyperopic individuals, including adults and children, underwent both cycloplegic and non-cycloplegic refraction as part of a comparative cross-sectional study. To compare refractive results between and within groups, data were examined using suitable non-parametric statistical tests. Results: The distribution of all the variables was not normal (p < 0.05). Both visual acuity (Z = -6.300, p = 0.000) and spherical equivalent (Z = -8.433, p = 0.000) showed statistically significant differences between cycloplegic and non-cycloplegic readings, with non-cycloplegic values consistently lower, according to within-group analysis. Cycloplegic SE, non-cycloplegic SE, and latent hyperopia showed significant differences between children and adults (p < 0.01) according to between-group analysis, however non-cycloplegic visual acuity showed no significant difference (p = 0.978). Compared to adults, children had higher mean rankings, which suggests more latent hyperopia. In both groups, cycloplegic refraction generally produced greater SE and VA values. Conclusion: When measuring refractive error, cycloplegic refraction is more accurate than non-cycloplegic refraction, which tends to underestimate hyperopia because of accommodating impact. In children, the discrepancy is more noticeable, underscoring the significance of cycloplegia in pediatric refractive evaluation. As a result, cycloplegic refraction should be regarded as crucial for the proper diagnosis and treatment of hyperopia, especially in younger populations.